Legal Reasoning Hakim Mahkamah Konstitusi dalam Putusan Mahkamah Konstitusi Nomor 62/PUU-XXII/2024 - Syaibani Ihza Ibrahim (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Constitutional Court Decision Number 62/PUU-XXII/2024 is a decision concerning the presidential and vice presidential nomination threshold. The existence of this decision is a breath of fresh air for political parties, where, in the absence of a presidential threshold, every political party can nominate a presidential and vice presidential candidate pair. However, it should be noted that judges in deciding the case do not immediately decide easily. There is something called legal reasoning that needs to be considered, because legal reasoning is a search for a basis or legal argument by a judge in dealing with the case. The research method used is the normative legal research method. By using the case approach method and the conceptual approach method. The results of the study show that legal reasoning is a method of finding a basis for legal argumentation or psychological processes of a judge in dealing with the case he is facing. The judges of the court, in deciding the Constitutional Court Decision Number 62/PUU-XXII/2024, used several interpretation methods to create legal reasoning. The methods used are the teleological interpretation method, the comparative interpretation method, the historical or original intent interpretation method, and the textual interpretation method.